2011
DOI: 10.2188/jea.je20090195
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Hospitalization Related to Motor Vehicle Accidents Among People Taking Zolpidem: A Case–Crossover Study

Abstract: BackgroundSeveral epidemiological and experimental studies have found a positive association between the risk of motor vehicle accidents (MVAs) and use of zopiclone and benzodiazepines. There is, however, little evidence of any risk of MVA attributable to the use of zolpidem 1 day before such accidents. We attempted to determine whether the use of zolpidem 1 day before is associated with an increased risk of an MVA.MethodsUsing a 1-million-person randomly sampled cohort from the Taiwan National Health Insuranc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 19 publications
0
33
1
Order By: Relevance
“…The odds of a next-day MVC hospitalization were 1.5-times higher among zolipdem users than nonusers, with a stronger association in males. (Yang et al 2011) Additionally, among a large Norwegian cohort selected from population-based registries, the standardized incidence of MVCs was more than 2-times higher among zolpidem users compared with nonusers. (Gustavsen et al 2008) In each of these studies, the association was stronger in males than females.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The odds of a next-day MVC hospitalization were 1.5-times higher among zolipdem users than nonusers, with a stronger association in males. (Yang et al 2011) Additionally, among a large Norwegian cohort selected from population-based registries, the standardized incidence of MVCs was more than 2-times higher among zolpidem users compared with nonusers. (Gustavsen et al 2008) In each of these studies, the association was stronger in males than females.…”
Section: Discussionmentioning
confidence: 99%
“…(Gustavsen et al 2008, Orriols et al 2011, Yang et al 2011, Chung et al 2013, Lai et al 2014) Gustavsen et. al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Post hoc, it was realized that some included studies only presented crude estimates, 63-82 while others adjusted their outcome measures for various potential confounders such as age, gender, miles driven, day of the week, etc. 83-89 For those studies that presented adjusted estimates or did not include 95% confidence intervals for crude estimates, 83-89 then the adjusted point estimates and 95% confidence intervals for the population were reported. If a study's point estimate was greater than 1, this indicated that there was excess risk of collision; a point estimate less than 1 indicated that the medication use was associated with a decreased risk of collision (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…A large-scale retrospective study using the Taiwanese National Insurance Health Database (Table 2) showed that use of zolpidem is associated with an increased risk of motor vehicle accidents in the following day (odds ratio ¼ 1.74; 95% confidence interval ¼ 1.25e2.43). 17 The acute performanceimpairing effects of zolpidem are comparable to those of benzodiazepines (BZDs), despite using different sample populations, methods of study, and different comparison drugs. 21 At doses as low as 7.5 mg in non-elderly participants, zolpidem has shown comparable dose-and time-dependent impairment in learning, recall, and performance.…”
Section: Performance Impairmentsmentioning
confidence: 99%